Implicit satiety goals and food-related expectations predict portion size in older adults: Findings from the BAMMBE cohort - Pink, Aimee E.; Lee, Li Ling; Low, Dorrain Yanwen; Yang, Yifan; Fong, Zoey LaiGuan; Kang, Alicia Yi Hui; Liu, Peijia; Kim, Hyejin; Wang, Yulan; Padmanabhan, Parasuraman; Cobiac, Lynne; Gulyas, Balazs; et al. (Elsevier, 2023)
Portion size selection is an indicator of appetite and within younger adults, is predicted by factors such as expected satiety, liking and motivations to achieve an ideal sensation of fullness (i.e., implicit satiety goals). Currently, there is limited research available on the determinants of portion size selection within older adults. Therefore, the current study aimed to examine the relationship between individual differences in implicit satiety goals, food-related expectations, and portion size selection in older adults. Free-living older adult Singaporeans (N = 115; Nmales = 62; age: M = 66.21 years, SD = 4.78, range = 60-83 years) participated as part of the Brain, Ageing, Microbiome, Muscle, Bone, and Exercise Study (BAMMBE). Participants completed questionnaires on their subjective requirements for experiencing different states of satiety and food-related expectations (i.e., liking, how filling) as well as a computerised portion size selection task. Using a multiple regression, we found that goals to feel comfortably full (B = 3.08, SE = 1.04, t = 2.96, p = .004) and to stop hunger (B = -2.25, SE = 0.82, t = -2.75, p = .007) significantly predicted larger portion size selection (R2 = 0.24, F(4,87) = 6.74, p < .001). Larger portion sizes (R2 = 0.53, F(5,90) = 20.58, p < .001) were also predicted by greater expected satiety (B = 0.47, SE = 0.09, t = 5.15, p < .001) and lower perceptions of how filling foods are (B = -2.92, SE = 0.77, t = -3.79, p < .001) but not liking (B = -0.09, SE = 0.91, t = -0.10, p = .925) or frequency (B = -18.42, SE = 16.91, t = -1.09, p = .279) of consumption of target foods. Comparing our findings to results of studies conducted with younger adults suggests the influence of factors such as satiety related goals on portion size selection may change with ageing while the influence of other factors (e.g., expected satiety/fullness delivered by foods) may remain consistent. These findings may inform future strategies to increase/decrease portion size accordingly to ensure older adults maintain an appropriate healthy weight.